2018
DOI: 10.4236/aid.2018.81003
|View full text |Cite
|
Sign up to set email alerts
|

A Scarce Presentation of <i>Mycobacterium tuberculosis</i>, Case Report

Abstract: Here, we report a case of 24-year-old female who experienced fever, weight loss, and headache by the termination of her pregnancy after 24 weeks. She was admitted due to multiple generalized tonic clonic (GTC) seizures and loss of consciousness. Her lab data and histological findings were insignificant as well as negative mycobacterium culture. Her brain MRI detected multiple enhanced brain lesions on T2 weighted images. Overall, she went under empiric anti-TB treatment for a year and had a complete recovery. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Studies regarding pregnant women reported that the risk of TB infection and its related post-partum complications are twice compared to other women. In fact, one study claimed that extra-pulmonary TB disease consisted 90% of post-partum tuberculosis [10]. Psychiatric symptoms like hallucination, psychosis, altered mental status are reported in case with intracranial tuberculosis along with usual symptoms like headache, seizure [11].…”
Section: Discussionmentioning
confidence: 99%
“…Studies regarding pregnant women reported that the risk of TB infection and its related post-partum complications are twice compared to other women. In fact, one study claimed that extra-pulmonary TB disease consisted 90% of post-partum tuberculosis [10]. Psychiatric symptoms like hallucination, psychosis, altered mental status are reported in case with intracranial tuberculosis along with usual symptoms like headache, seizure [11].…”
Section: Discussionmentioning
confidence: 99%